Using of molecular genetics techniques in poultry breeding: Subject review - Ismail Y. AL-Hadeedy; Sarmad T. Abdulazeez; Mohammed A. Mohammed; Imad M. Al-Jabari (Zien Journals, 2023)
Adopting modern molecular biology techniques to improve bird productivity by focusing on the behavior of the target gene has become a more efficient and more important method in poultry breeding programs, as it is difficult to achieve rapid progress using traditional methods of genetic breeding that depend on the phenotype, which expresses to the genotype carried by the bird. And then selecting the best birds based on phenotype and making those birds parents of next generation by mating them. This process takes a long time, arduous effort and high economic cost, until the molecular genetics techniques used that depend on discover the genes carried by the bird in cell nucleus and thus early prediction of productivity of birds without need for field breeding or depends on phenotype and thus reduce effort, time and the cost of breeding that takes several generations. The revolution in the using molecular genetics techniques began in the twentieth century, specifically in 1966, when the genetic locus of quantitative traits was revealed that are considered more important in farm animals, and what resulted then in extraction of DNA, which contributed to identifying the chromosomal locus that affect the traits, followed by the ability to multiplied DNA by using PCR techniques for the first time in 1983. Then RFLP technology was discovered, which developed DNA maps resulting from genetic variation by using restriction enzymes, this technology resulted in creation of famous chicken breeding commercial company Hy-Line International. Then came the third-generation techniques of molecular genetics known as SNP techniques, which were discovered in 1990 and considered important because it is suitable for showing phenotypic diversity that cannot be reached by other types of markers. From the foregoing, it appears that there is a revolution upcoming in the field of using modern molecular genetics technologies as a means of selection in poultry, and for those reasons this subject review was done
Keywords: molecular genetics; selection; DNA extraction